2011
DOI: 10.2528/pier10100707
|View full text |Cite
|
Sign up to set email alerts
|

Half Mode Microwave Filters Based on Epsilon Near Zero and Mu Near Zero Concepts

Abstract: Abstract-A new design of microwave band pass filter design is presented using metamaterial-inspired Epsilon Near Zero (ENZ) and Mu Near Zero (MNZ) behaviors. These filters are based on waveguide technology. The proposed structure allows us to reduce the number of tunnels normally used for passband filter design by reducing its size. It is also incorporated the half mode concept to the tunnels leading a greater miniaturization. Two Chebyshev filters with two and fourpoles were designed, fabricated and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Such an effect can be obtained by coupling a narrow-height waveguide in its propagation mode. Although the coupling is originally made using different-height waveguides to produce squeezing of the energy along the tunnel [7], it is demonstrated that, over the planar SIW technology, the effect can be obtained using transmission lines as coupling elements [17], [18].…”
Section: B Sensor-b (Siw Tunnel Sensor)mentioning
confidence: 99%
“…Such an effect can be obtained by coupling a narrow-height waveguide in its propagation mode. Although the coupling is originally made using different-height waveguides to produce squeezing of the energy along the tunnel [7], it is demonstrated that, over the planar SIW technology, the effect can be obtained using transmission lines as coupling elements [17], [18].…”
Section: B Sensor-b (Siw Tunnel Sensor)mentioning
confidence: 99%
“…Although the methodologies for designing filters of various configurations have been known for decades, researchers are still introducing new solutions [1][2][3][4][5][6][7][8]. Depending on filter technology, frequency band and production quality filters have to be tuned or are ready for use directly after manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The methodologies for designing microwave filters are known for a long time but a lot of researchers are still introducing new solutions (cf. [7][8][9][10][11][12][13][14]). In this paper, we are focusing on the related problem of coupling coupling matrix extraction.…”
Section: Introductionmentioning
confidence: 99%